Saint Francis of Assisi Passion, Poverty & the Man Who Transformed the Church. - Thoman, Bret. (St. Benedict Press LLC, 2016)
All Christians know his name. Few truly know the man. Francis of Assisi was not even five feet tall. He was not well educated. And yet he is the one saint commonly recognized as Alter Christus, the "other Christ." Francis is not just any saint--he's a saint for everyone, whatever your place or position in life. But do we really know him? Who was this man at his core? What was it that thrust this little man from a little town to the heights of sanctity, into a place of high honor among the celestial court? In this riveting biography, author Bret Thoman accomplishes what few biographers have. He pierces the inner life of Francis, revealing his deepest passions, his unquenchable love for poverty, and his unshakable grip on the core of the Gospel. The life of Francis, so often festooned with spectacle and miracle, is in reality the story of a soul yearning for God in every moment and glimpsing His presence in all creation. If you want to see the hidden life of the greatest saint, if you want to hear his thoughts, if you want to feel the fervor that blazed within his soul, you must readSt. Francis of Assisi: Passion, Poverty, and the Man who Transformed the Catholic Church.
Title Page; Copyright Page; Dedication; Contents; Foreword; Preface; Acknowledgments; 1. Nativity; 2. War; 3. From War to Obedience in Spoleto; 4. Humility and San Damiano; 5. Leprosy and Minority; 6. The Crucifix Speaks; 7. Spiritual Sword; 8. Go Forth: Through Creation to Gubbio; 9. Poverty and the Portiuncula; 10. Evangelization and Brother Bernard; 11. Community and Rivotorto; 12. To Rome; 13. Praying in the Hermitage; 14. On Pilgrimage; 15. Peace and the Sultan; 16. Incarnation and Greccio; 17. Stigmata and Laverna; 18. Transitus; The Canticle of the Creatures; About the Author; Index.
Print version record.
Keywords: Francis, -- of Assisi, Saint, -- 1182-1226.; Francis, -- of Assisi, Saint, -- 1182-1226.; RELIGION / Institutions & Organizations; Electronic books